Botox as an adjunct to lip repositioning for the management of excessive gingival display in the presence of hypermobility of upper lip and vertical maxillary excess - Lobna Abdel Aziz Aly; Nelly Ibrahim Hammouda (Dental Research Journal, 2016)
Background: Excessive gingival display (GD) is a frequent finding that can occur because of various intraoral or extraoral etiologies. This work describes the use of a mucosal repositioned flap for the management of a gummy smile associated with vertical maxillary excess (VME) and hypermobility of the upper lip followed by injection of Botox. Materials and Methods: Seven female patients in the age range of 17–25 years presented with a gummy smile. At full smile, the average GD ranged from 6 to 8 mm. A clinical examination revealed hypermobility of the upper lip. A cephalometric analysis pointed to the presence of VME. The mucosal repositioned flap surgery was conducted followed by injection with botulinum toxin type A (Botox) 2 weeks postsurgically. Results: After 4 weeks, results were definitely observed with a decrease from 8 mm gingival exposure to 3 mm, which was considered as normal GD for an adult during smiling. Conclusion: For patients desiring a less invasive alternative to orthognathic surgery, the mucosal repositioned flap is a viable alternative. Moreover, Botox is a useful adjunct to enhance the esthetics and improve patient satisfaction where surgery alone may prove inadequately in moderate VME.